IMPLEMENTATION OF ALQURAN TAHSIN LEARNING METHOD FOR MTS AL-MUNAWWARAH BINJAI CLASSROOMS STUDENTS BINJAI REGENCY NORTH SUMATERA PROVINCE - Sinaga, Ali Imran; Salim, Salim; Habibi, Rozaq (Universitas Dharmawangsa Medan, 2021)
The objectives of this study were: 1) To determine the implementation of the MTs students' implementation of the Tahsin Al-Qur'an learning method. Al-Munawwaroh Binjai, Jackfruit Village, North Binjai District, 2) To find out the obstacles in the implementation of the MTs students' implementation of the Quranic tahsin learning method. Al-Munawwaroh Binjai, Nangka sub-district, North Binjai District, 3) To find out the solution taken in overcoming the problem of implementing the learning method for MTs students. Al-Munawwaroh Binjai, Jackfruit Village, North Binjai District. This research is a qualitative research with a case study approach, which examines a particular case or phenomenon in society that is carried out in depth to be able to find out the background, circumstances, and interactions that occur.Â The results of this study are 1) Implementation of the MTs students' implementation of the Qur'anic tahsin learning method. Al-Munawwaroh Binjai, jackfruit sub-district, Binjai Utara district, namely the implementation of the tahsin learning method used varies, but in this implementation it is specifically applied with the iqra method. The iqra method is a quick way to read the Koran through several volumes, from volume one to volume six. This method is more effective in escorting children to be able to quickly read the Koran well, 2) Obstacles in implementing the learning method for MTs students. Al-Munawwaroh Binjai, Kelurahan jackfruit, Binjai Utara District is not included in the iqro method of introducing the term Tajweed, but only how to read it, besides that there are also two factors, namely First, internal factors (factors that come from within) such as the lack of self-awareness of the participants. students in following the real Qur'anic tahsin learning. Then there are still many students whose ability to read the Koran is still halting. Second, external factors (factors that come from outside) such as the role of the tahsin teacher in providing teaching to students, the participation of parents in guiding and supervising their children, as well as the influence of the surrounding environment which can have a positive or even negative influence on students. 3) The solution is made in overcoming the problem of implementing the learning method of the Islamic teaching of the Qur'an for MTs students. Al-Munawwaroh Binjai, Nangka Subdistrict, Binjai Utara District.